A unique pulmonary venous abnormality: with associated pulmonary arterial anomaly and arteriovenous malformation. Issue 2 (April 1976) - Honey, M; Pearson, M C; Pattinson, J N
Abstract : A man aged 29 was first seen at the age of 11, when he was found to have a congenital anomaly of the pulmonary veins which follow an abnormal course to the hilum. On the left side, two large veins descend peripherally before turning medially towards the left atrium; on the right, several smaller veins follow a similar circuitous route from the periphery, before uniting into two main veins which enter the left atrium. The proximal pulmonary arteries are normal in their pattern of branching and distribution but are dilated and tortous and taper abruptly: the left lower lobe artery is abnormally large almost down to the diaphragm. There is also a systemic arterio/pulmonary venous fistula. There is no haemodynamic disturbance, but gas transfer is slightly impaired, and there is slight arterial desaturation. The congenital anomaly is unique. Reported cases described as having pulmonary venous varices are a heterogeneous group, but one patient described as such shows resemblances to our case.